The Effect of Lavender Aromatherapy on Insomnia among the Elderly at Al-Maun Muhammadiyah Elderly Center - Kharistie Ulva Septa; Arjuna Arjuna; Tasya Anggraini (Inspirasi Foundation, 2027)
Introduction: Insomnia is a sleep disorder characterized by difficulty falling asleep, difficulty maintaining sleep, and sleep that does not provide a feeling of refreshment or adequate rest, especially if it lasts for a month or more. At the Al-Maun Muhammadiyah elderly care center, there are 10 elderly people experiencing insomnia. Objective: This study aims to determine the effect of lavender aromatherapy on elderly people with insomnia at the Al-Maun Muhammadiyah elderly care center in Belitung Regency, Tanjungpandan District, in 2025. Method: This study was conducted using a pre-experimental design, namely with a one-group pretest and posttest model and Shapiro-Wilk with the results in the form of univariate and bivariate analysis. The population in this study were elderly aged 60-90 years who lived in the Al-Maun Muhammadiyah elderly home, Belitung Regency, Tanjungpandan District in 2025. The sample in this study was a portion of the research population, totaling 10 Result: The results of this study showed an average insomnia score before treatment of 26.10 ± 1.449, which decreased to 17.60 ± 2.271 after treatment. A p-value of 0.005 indicates statistical significance (p<0.05). Conclusion: The conclusion of this study is that lavender aromatherapy has an effect on elderly people with insomnia at the Al-Maun Muhammadiyah Elderly Home in Belitung Regency, Tanjungpandan District, in 2025.